Sustainable pilgrimage tourism – inclusive religious sanctuaries chart (irsch) - Gołębieska, Karolina; Ostrowska-Tryzno, Anna; Pawlikowska-Piechotka, Anna (Studia Ecologiae et Bioethicae, 2018)
Knowing the extent of the detailed conditions for sustainable development of culture – religion tourism seems to be an important issue, because interest in religious tourism, pilgrimages, cultural and religious tourism in Poland seemed to be unabated. Among millions of tourists annually visiting the most popular sanctuaries, many are people with different kind of disabilities, elders and families with toddlers. However the issue was not yet a material for broader and deeper scientific studies in Poland. Weight of the precise of discernment seemed to be particularly important in the context of pilgrims expected in Poland in 2016, on the occasion of World Youth Day, as well as in subsequent years, what will be the likely consequence of this year’s celebrations. One of the most important outcomes of the study is the ‘Inclusive Religious Sanctuaries Chart’ (IRSCH), helpful with identification of the material and non-material barriers. In this text the authors present the findings of research carried out under ds-144 and ds.-245 AWF Warsaw projects (Ministry of Science and Higher Education grants for the years 2014-2018).